2015
DOI: 10.1038/mi.2014.122
|View full text |Cite
|
Sign up to set email alerts
|

PTPN2 controls differentiation of CD4+ T cells and limits intestinal inflammation and intestinal dysbiosis

Abstract: Loss-of-function variants within the gene locus encoding protein tyrosine phosphatase non-receptor type 2 (PTPN2) are associated with increased risk for Crohn's disease (CD). A disturbed regulation of T helper (Th) cell responses causing loss of tolerance against self- or commensal-derived antigens and an altered intestinal microbiota plays a pivotal role in CD pathogenesis. Loss of PTPN2 in the T-cell compartment causes enhanced induction of Th1 and Th17 cells, but impaired induction of regulatory T cells (Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
128
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(139 citation statements)
references
References 49 publications
(61 reference statements)
9
128
2
Order By: Relevance
“…Spalinger et al reported that loss of PTPN2 in the T-cell compartment caused enhanced induction of Th1 and Th17 cells, but impaired induction of Treg in several mouse colitis models [22]. We found the expression of PTPN2 was significantly decreased in diabetic EWAT.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…Spalinger et al reported that loss of PTPN2 in the T-cell compartment caused enhanced induction of Th1 and Th17 cells, but impaired induction of Treg in several mouse colitis models [22]. We found the expression of PTPN2 was significantly decreased in diabetic EWAT.…”
Section: Discussionsupporting
confidence: 61%
“…PTPN2 might be the key regulator that controls the T cells polarization [22, 23]. Spalinger et al reported that loss of PTPN2 in the T-cell compartment caused enhanced induction of Th1 and Th17 cells, but impaired induction of Treg in several mouse colitis models [22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations